Electroactive Bacteria Associated With Stainless Steel Ennoblement in Seawater - Trigodet, Florian; Larché, Nicolas; Morrison, Hilary G.; Jebbar, Mohamed; Thierry, Dominique; Maignien, Loïs (Frontiers in microbiology, 2019)
Microorganisms can increase the open-circuit potential of stainless steel immersed in seawater of several hundred millivolts in a phenomenon called ennoblement. It raises the chance of corrosion as the open-circuit potential may go over the pitting corrosion potential. Despite the large impact of the ennoblement, no unifying mechanisms have been described as responsible for the phenomenon. Here we show that the strict electrotroph bacterium " Tenderia electrophaga" is detected as an ennoblement biomarker and is only present at temperatures at which we observe ennoblement. This bacterium was previously enriched in biocathode systems. Our results suggest that " Tenderia electrophaga," and its previously described extracellular electron transfer metabolism coupled to oxygen reduction activity, could play a central role in modulating stainless steel open-circuit potential and consequently mediating ennoblement.